2020
DOI: 10.1177/2151459320946013
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Sagging After Cephalomedullary Nailing for Intertrochanteric Femur Fracture is Associated with a Separation of the Greater Trochanter

Abstract: Introduction: Cephalomedullary nailing presents several biomechanical benefits for treatment of intertrochanteric fractures, but posterior sagging (PS) of the proximal fragment occurs postoperatively in some patients despite intraoperative achievement of an adequate reduction. We investigated the risk factors for PS in those patients, with specific attention to posterior split fragment involving the greater trochanter (GT separation) as a possible significant risk factor. Methods: We retrospectively reviewed 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For the quality of fracture reduction, there has been a recent tendency for surgeons to pay more attention to the anteromedial cortex rather than to the posteromedial lesser trochanter, as has been previously described [ 31 ]. In addition, Kim et al [ 32 ] showed that greater trochanter separation was a risk factor for posterior sagging, which was caused by the instability of the posterior coronal fragment. Parry et al [ 33 ] demonstrated that calcar gapping and fracture classification were related to over-sliding of lag screws.…”
Section: Discussionmentioning
confidence: 99%
“…For the quality of fracture reduction, there has been a recent tendency for surgeons to pay more attention to the anteromedial cortex rather than to the posteromedial lesser trochanter, as has been previously described [ 31 ]. In addition, Kim et al [ 32 ] showed that greater trochanter separation was a risk factor for posterior sagging, which was caused by the instability of the posterior coronal fragment. Parry et al [ 33 ] demonstrated that calcar gapping and fracture classification were related to over-sliding of lag screws.…”
Section: Discussionmentioning
confidence: 99%
“…C ustom-made synthetic osteoporotic bone samples that were designed with use of previously created computed tomography (CT) images of human hips (Tanac) were used in this study. These samples had a neck-shaft angle of 135°, anteversion of 25.8°, cancellous bone density of 7.5 pounds per cubic foot (pcf) (0.115 g/cm 3 ), cortical bone density of 60 pcf (0.92 g/cm 3 ), and a canal flare index (CFI) of 2.29. Two types of fracture lines were created.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Furthermore, recent studies have shown that posterolateral fracture lines of trochanteric femoral fractures cause posterolateral instability [11][12][13][14] . Kim et al and Suzuki et al reported that the presence of a posterolateral fracture increases the risk of postoperative fragment displacement, resulting in a higher rate of implant failure and/or nonunion 3,15 . However, the etiology of instability associated with a posterolateral fracture morphology remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be divided into stable and unstable fractures in Evans typing, which is mainly based on the integrity and continuity of the posterior inner wall cortex. After the stable interrotor fracture, the internal wall is intact or with a very small displacement, and the unstable interrotor fracture after the internal wall is comminuted (13). There is also a special classification in this classification.…”
Section: Introductionmentioning
confidence: 99%